Massification of Higher Education in Asia Consequences, Policy Responses and Changing Governance (Higher Education in Asia: Quality, Excellence and Governance, 2018)
This book addresses important questions and puzzles regarding the massification of higher education in Asia. It equips readers to critically evaluate and understand the consequences and challenges that massification entails, while also prompting policymakers and higher education administrators to tackle emerging issues related to the massification of higher education. Readers will gain a deeper, nuanced understanding of this trend, including its impacts and governance issues.